Analysis of particulate matter emission in diesel engine operated with waste cooking oil biodiesel - Nur Fauziah, Jaharudin (2015)
Diesel engines which is an attractive power unit used widely in many fields are among the main contributors to air pollutions for the large amount of emissions, especially particulate matter (PM) and nitrogen oxides (NOx). PM is one of the major pollutants emitted by diesel engine which have adverse effects on human health. Accordingly, many research have been done to find alternative fuels that are clean and efficient. In this study, waste cooking oil (WCO) biodiesel has been used as an alternative source for diesel engine which produces lower PM than diesel fuel. The emission of PM and gaseous emission (carbon monoxide (CO), carbon dioxide (CO2), nitric oxide (NO) and NOx) has been collected from single cylinder diesel engine fuelled with diesel and WCO biodiesel blends (B5, B10 B20 and B100) at five different engine speed (1200 rpm, 1500 rpm, 1800 rpm, 2100 rpm and 2400 rpm) with constant load of 20 Nm. The comparison between diesel and WCO biodiesel blends has been made in terms of PM characterization which is PM mass concentration, its component (soluble organic fraction (SOF) and soot) and its influence on PM formation, PM morphology and PM size distribution. In addition, combustion characteristic which is in-cylinder pressure of the engine as well as exhaust temperature also has been observed. The results show PM emission of B100 is lower than diesel fuel with variation of 5.56% to 21.82 % . This is due to oxygen content contained in B100. As for SOF concentration, blended fuels B10, B20, and B100 have higher SOF value (3.23 % to 82.36 % ) compared to diesel fuel at moderate and high engine speed. Meanwhile, soot concentration for blended fuels B10, B20 and B100 is lower (10 % to 62.50 %. ) compared to diesel fuel Observation on PM morphology shows that the images is chain-like agglomeration which is extremely small non uniform nanostructure. As for the PM size distribution, the trend were similar for diesel and WCO biodiesel blends. The size distribution of diesel fuel and WCO biodiesel blends were shifted to the larger size as the engine speed is increased. Simultaneously, the size distribution is shifted to the smaller PM diameter as blending ratio of WCO biodiesel in the fuel blend is increase. The observation of in-cylinder pressure shows uncertain trend with the WCO biodiesel ratio in the fuel blend while decreasing with the increasing engine speed due to the prolong ignition delay period. At the same time, WCO biodiesel blends gives higher value of exhaust temperature which is 1.49 % compared to diesel fuel and it increases as the engine speed increase. In terms of gaseous emission, increasing engine speed increased the CO, CO2, NOx and NO emission while decrease the O2 emission. The effect of WCO biodiesel blends on the gaseous emission shows uncertain trend while PM-NOx trade off observation shows B100 simultaneously decrease both NOx and PM emission at the same time. This study shows that the PM and gaseous emission as well as combustion characteristic of the WCO biodiesel are comparable with diesel fuel thus WCO biodiesel has potential as an alternative fuel to be used in diesel in the future.